Altered intra- and inter-network functional connectivity in patients with persistent postural-perceptual dizziness - Li, Kangzhi (Neuroimage Clin, 2020)
BACKGROUND: Persistent postural-perceptual dizziness (PPPD) is a functional vestibular disorder characterized by persistent dizziness, unsteadiness, and non-spinning vertigo. It is the most common cause of chronic vestibular syndrome, but its pathogenesis is currently unclear. Recent studies have indicated that sensory integration may be altered in PPPD patients. OBJECTIVE: Using independent component analysis (ICA) combined with seed-based functional connectivity analysis, we aimed to analyze changes in brain network functional connectivity (FC) in PPPD patients during the resting state and to explore the underlying pathogenesis of PPPD, particularly the abnormal integration of multiple sensations. METHODS: Study subjects included 12 PPPD patients and 12 healthy controls and were recruited from January to August 2018. Detailed medical data were collected from all participants. Vestibular function, neurological and medical examinations were conducted to exclude other diseases associated with chronic dizziness. Functional MRI was performed on all subjects. ICA and seed-based functional connectivity analysis were performed to examine changes in intra- and inter-network FC in PPPD patients. RESULTS: In total, 13 independent components were identified using ICA. Compared with healthy controls, PPPD patients showed decreased intra-network FC in the right precuneus within the posterior default mode network. Moreover, seed-based functional connectivity analysis showed decreased intra-network FC between the right precuneus and the bilateral precuneus and left premotor cortex, and enhanced FC between the right precuneus and bilateral corpus callosum. With respect to the inter-network, FC in PPPD patients was increased between the occipital pole visual network and auditory, sensorimotor networks, as well as the lateral visual and auditory networks. Additional analyses showed that FC changes were negatively correlated with dizziness handicap inventory functional scores. CONCLUSION: In PPPD patients, dysfunction in the precuneus may cause abnormalities in external environment monitoring and in posture and movement regulation. Compensatory strategies may then be adopted to maintain balance. At the local level, information exchange between the two cerebral hemispheres is enhanced via the corpus callosum. At the whole brain level, through enhancement of functional activities of the visual network, the integration of multiple sensations and the regulation of posture and movement are primarily driven by visual information.